Parole System Reducing the Overcrowding Situation of Prisoners in Kathmandu Valley - Dhungana, Mukesh; Phuyal, Samjhana (Kathmandu School of Law Review, 2021)
The Parole system is one of the alternative models of reforming the prison system under the criminal justice system. It has been found that prisoners in the prison of Kathmandu valley are overcrowded and even the prison is not properly managed. Prisoners are facing multiple impacts from such situations of prison being overcrowded. Therefore, this article aims to explore the situation of prison being overcrowded, the reasons behind and its effects. It also aims to explore the implementation status and re-define the role and responsibilities of concerned authorities including the Home Ministry, Prison Management Department, and prisons in Kathmandu valley. The parole system has recently been introduced in Nepal as an alternative mechanism to imprisonment. The Criminal offences (Sentencing and Executing) Act 2074 has elaborated on the prison system and such alternatives.